2021
DOI: 10.1155/2021/8814890
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals of Rhus spp. as Potential Inhibitors of the SARS-CoV-2 Main Protease: Molecular Docking and Drug-Likeness Study

Abstract: Background. The outbreak of coronavirus disease 2019 (COVID-19) induced by the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) originated in China and spread to cover the entire world with an ongoing pandemic. The magnitude of the situation and the fast spread of the new and deadly virus, as well as the lack of specific treatment, led to a focus on research to discover new therapeutic agents. Aim. In this study, we explore the potential inhibitory effects of some active polypheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…studied the antiviral activity of 26 active polyphenolic compounds of Rhus spp . against SARS-CoV-2 main protease enzyme (M pro ; 6LU7) using molecular docking approach and identified six polyphenolic compounds as potential inhibitors based on drug likeness, solubility in water, and synthetic accessibility score (SAS) analysis ( Sherif, Gabr, Hosny, Alghadir, & Alansari, 2021 ). These polyphenols mainly interact through H-bonding, whereas, in our study, 1,3,6-Trigalloyl glucose, Beta-Sitosterol and Daucosterol interact primarily through hydrophobic residues along with H-bonding.…”
Section: Discussionmentioning
confidence: 99%
“…studied the antiviral activity of 26 active polyphenolic compounds of Rhus spp . against SARS-CoV-2 main protease enzyme (M pro ; 6LU7) using molecular docking approach and identified six polyphenolic compounds as potential inhibitors based on drug likeness, solubility in water, and synthetic accessibility score (SAS) analysis ( Sherif, Gabr, Hosny, Alghadir, & Alansari, 2021 ). These polyphenols mainly interact through H-bonding, whereas, in our study, 1,3,6-Trigalloyl glucose, Beta-Sitosterol and Daucosterol interact primarily through hydrophobic residues along with H-bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Specific areas of proteins are also investigated such as the protease domain (PD) of ACE2, the RBD (which binds to PD) of S protein ( Albohy et al, 2020 ), S1 (contains the RBD) and S2 (responsible for membrane fusion subsequent to the role of S1) subunit protein ( Harisna et al, 2021 ; Verma et al, 2020 ), and the protease enzyme 6LU7, which is the crystal structure of the 3CLpro ( Sherif et al, 2021 ). Arokiyaraj et al (2020) determined that kaempferol, kaempferol 7-o-rhamnoside, quercetin, kaempferitrin, geraniin, corilagin, protocatechuic acid, gallic acid and ellagic acid are compounds with the potential to inhibit the RBD activity of S protein of the SARS-CoV-2.…”
Section: Methodsmentioning
confidence: 99%
“… ACE2: (K353, D30, D38, E35, E37 and N33) a . Sherif et al (2021) Rhus spp . Methyl 3,4,5-trihydroxybenzoate Protease enzyme 6LU7 −81.82 (His164, Leu141¸ Cys145, Ser144 and Phe140) a .…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that several natural compounds and their derivatives were effective against SARS-CoV-2 infection ( Supplementary Table 5 [ 147 , 148 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ]) [ 160–163 ]. It has been documented that a number of herbal extracts belonging to the Polygonaceae family inhibit the interaction of viral S protein with host ACE2 [ 164 ], and one such example is emodin [ 165 ].…”
Section: Natural Compounds Dietary Supplements and Nutraceuticals Aga...mentioning
confidence: 99%